Comparative effectiveness of semaglutide versus liraglutide, dulaglutide or tirzepatide: a systematic review and meta-analysis - Karimi, Mohammad Amin; Gholami Chahkand, Mohammad Sadra; Dadkhah, Parisa Alsadat; Sheikhzadeh, Farzad; Yaghoubi, Shayan; Esmaeilpour Moallem, Fatemeh; Deyhimi, Mitra Sadat; Arab Bafrani, Melika; Shahrokhi, Mehregan; Nasrollahizadeh, Amir (Frontiers in Pharmacology, 2025)
BackgroundThis study seeks to compare the effectiveness of Semaglutide compared to Liraglutide, Dulaglutide, or Tirzepatide. Additionally, it aims to investigate the implications of transitioning from Dulaglutide or Liraglutide to Semaglutide.MethodsWe searched PubMed, Scopus, Cochrane Library, Google Scholar, and Web of Science (ClinicalTrials.gov for unpublished records) from their inception to 5 February 2025, including observational cohort studies and randomized controlled trials. Analyses were conducted using Review Manager (RevMan) version 5.4.1 and STATA 17.ResultsThe meta-analysis comprised 16 studies and 5,997 patients. Semaglutide significantly reduced hemoglobin A1c (HbA1c) levels compared to Liraglutide (0.56; 95% CI: 0.19–0.94; p < 0.001). However, no significant differences were observed between Semaglutide and Liraglutide in terms of fasting blood sugar (FBS), body mass index (BMI), and weight change. In comparison to Dulaglutide, Semaglutide displayed superior efficacy in reducing HbA1c levels (3.72; 95% CI: 0.02–7.41; p = 0.05) and FBS (2.66; 95% CI: 0.26–5.07; p = 0.03). However, no significant differences were found in weight and BMI change. Tirzepatide exhibited a notable advantage over Semaglutide in reducing HbA1c levels (−0.45; 95% CI: −0.88 to −0.02; p = 0.04). However, no clear superiority was observed for weight and FBS change. Transitions from Liraglutide to Semaglutide did not significantly impact HbA1c levels. However, weight loss (2.48; 95% CI: 0.45–4.51; p = 0.02) and reduced FBS levels (10.76; 95% CI: 0.55–20; p = 0.04) were observed. Transitioning from Dulaglutide to Semaglutide did not significantly affect HbA1c levels and weight change.ConclusionWhile the precise source of heterogeneity remains elusive across most studies, analyses consistently demonstrate Semaglutide’s superior efficacy compared to Liraglutide in reducing both HbA1c levels and weight. Moreover, it presents advantages over Dulaglutide, specifically in lowering FBS levels. However, Tirzepatide surpasses Semaglutide in its efficacy for reducing HbA1c levels.